Praktik Ijarah pada PT. Adira Finance TBK : Kajian Fatwa DSN-MUI - Saslia, Eva; Kamaruddin, Kamaruddin; Possumah, Bayu Taufiq; Majid, Jamaluddin; Wawo, Andi (Tangible Journal, 2025)
This study aims to analyze the practice of the ijarah contract at PT. Adira Finance Tbk and assess its compliance with the provisions of DSN–MUI fatwas. The research employs a qualitative approach using the content analysis method to interpret information obtained from official corporate documents. The data used in this study are secondary data, with the main data source being the 2023 Financial Report of PT. Adira Finance Tbk. The initial assumPT.ion suggested that the Sharia unit of Adira Finance implemented a standard ijarah contract; however, the analysis reveals that the contract actually applied is Ijarah Muntahiyah Bi Tamlik (IMBT), a derivative of ijarah that concludes with the transfer of asset ownership. The application of IMBT is reflected through asset recognition, amortization mechanisms, and ujrah revenue recognition in accordance with DSN–MUI Fatwa No. 27/2002 and PSAK 107 on Ijarah Accounting. These findings indicate that Adira Finance Syariah has consistently implemented the developed form of the ijarah principle in compliance with both sharia regulations and modern accounting standards.